Decree of the president of Arab republic of Egypt No. 538 of the Year 2016 Amending The Harmonized Customs Traffif = قرار رئيس جمهورية مصر العربية رقم 538 لسنة 2016 بتعديل التعريفة الجمركية المنسقة / presidency - Egypt. presidency (2025)
Decree the President of the Arab Republic of Egypt No. 538 of the Year 2016 قرار رئيس جمهورية مصر العربية رقم 538 لسنة 2016